I12: the Joint Engineering, Environment and Processing (JEEP) beamline at Diamond Light Source. (7th April 2015) - Drakopoulos, Michael; Connolley, Thomas; Reinhard, Christina; Atwood, Robert; Magdysyuk, Oxana; Vo, Nghia; Hart, Michael; Connor, Leigh; Humphreys, Bob; Howell, George; Davies, Steve; Hill, Tim; et al.
<x xml:space="preserve">Abstract</x> I12 is the Joint Engineering, Environmental and Processing (JEEP) beamline, constructed during Phase II of the Diamond Light Source. I12 is located on a short (5 m) straight section of the Diamond storage ring and uses a 4.2 T superconducting wiggler to provide polychromatic and monochromatic X‐rays in the energy range 50–150 keV. The beam energy enables good penetration through large or dense samples, combined with a large beam size (1 mrad horizontally × 0.3 mrad vertically). The beam characteristics permit the study of materials and processes inside environmental chambers without unacceptable attenuation of the beam and without the need to use sample sizes which are atypically small for the process under study. X‐ray techniques available to users are radiography, tomography, energy‐dispersive diffraction, monochromatic and white‐beam two‐dimensional diffraction/scattering and small‐angle X‐ray scattering. Since commencing operations in November 2009, I12 has established a broad user community in materials science and processing, chemical processing, biomedical engineering, civil engineering, environmental science, palaeontology and physics.